The Role of GABAergic Inhibition in Ocular Dominance Plasticity - J. Alexander Heimel; Daniëlle van Versendaal; Christiaan N. Levelt (Neural Plasticity)
During the last decade, we have gained much insight into the mechanisms that open and close a sensitive period of plasticity in the visual cortex. This brings the hope that novel treatments can be developed for brain injuries requiring renewed plasticity potential and neurodevelopmental brain disorders caused by defective synaptic plasticity. One of the central mechanisms responsible for opening the sensitive period is the maturation of inhibitory innervation. Many molecular and cellular events have been identified that drive this developmental process, including signaling through BDNF and IGF-1, transcriptional control by OTX2, maturation of the extracellular matrix, and GABA-regulated inhibitory synapse formation. The mechanisms through which the development of inhibitory innervation triggers and potentially closes the sensitive period may involve plasticity of inhibitory inputs or permissive regulation of excitatory synapse plasticity. Here, we discuss the current state of knowledge in the field and open questions to be addressed.